(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper examines the role of Dewan Vishweshwariah in conceiving the University of Mysore as an apex institution of higher education. He dreamt of making Mysore a place of educational & industrial growth. Mysore University was the seventh University to be established in India and the very first in any princely States of India. There were several deliberations towards establishing a university in Mysore because the permission of British Government in Madras has to be sought before going on with the project. With a strict mindset Dewan Vishweshwariah progressed with this project & was successful in making Princely state of Mysore, the first Princely state to own a University. The credit goes directly to Dewan Vishweshwariah for making a scholastic move entailing great perseverance & determination. This paper focuses on Dewan Vishweshwariah & his vision of Mysore university